Perry aboard the alley cat's ferry - Dayon, Gab; Ananayo, Aizel (2023)
"Perry, a bisexual atheist born in the Philippines, finds herself confused after watching a triggering commercial on another channel. After falling asleep, Perry wakes up on a ferry and is welcomed by a black cat named Willa (who also happens to be a character from her favorite show, 'Animal Friends'). Unconsciously pre-determining her ferry routes, Perry and the cat explored many places that explained her religious and sexual identity in relation to culture. Faced with confusion and questions, the young Perry grew more mature as she returned to her Inang Bayan. As she wakes up from the dream. Perry now recognizes her identity and the identities of others with respect to their culture."--Back cover.